METAPHOR AND METONYMY IN ENGLISH AND UZBEK PROVERBS FORMED ON THE BASIS OF MEDICAL LEXICON (TAMADDUN NURI JURNALI, 2024)
This article provides a deeper analysis of the meanings and uses of the lexemes “injury” and “wound” in English, as well as “yara” and “jarohat” in Uzbek. These lexemes can express not only physical damage to the human body but also psychological and social harm. The article examines the unique characteristics and distinctions of “injury” and “wound,” and “yara” and “jarohat” lexemes as well as their application in metaphors and metonymies. Furthermore, it discusses proverbs that utilize these lexemes and their cultural and social meanings.